Correction: Shafiq et al. Titanium Oxide and Zinc Oxide Nanoparticles in Combination with Cadmium Tolerant Bacillus pumilus Ameliorates the Cadmium Toxicity in Maize. Antioxidants 2022, 11, 2156 - Tayyab Shafiq; Humaira Yasmin; Zafar Abbas Shah; Asia Nosheen; Parvaiz Ahmad; Prashant Kaushik; Ajaz Ahmad (Antioxidants)
In the original publication [...]